2021
DOI: 10.1016/j.tipsro.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in radiation therapist/therapeutic radiographer (RTT) advanced practice (AP) roles delivering on the four domains

Abstract: Introduction: Advanced practice roles are well documented, and continue to respond to the changing landscape in radiotherapy and oncology. In the UK the highest level of AP for the therapeutic radiographer/radiation therapist (RTT) is the consultant radiographer. These posts should meet the four domains of practice, as set out in national guidance. Here we aim to describe well established roles that meet this criteria, and provide subgroups of examples. Methodology: Three AP post holders with over 10 years AP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…12,44,45 A total of eight of the included studies were UK-based and outlined the steps to implementation of an APRT role in the UK. 21,23,24,32,35,36,42,43 These papers discussed the four step APRT framework established by the UK called the 'four domains of practice'. These four domains are set out by national guidance and comprise the following domains: Eleven of the studies reported on the establishment of an APRT role in Canada, 8,14,17,19,22,26,[29][30][31]33,35 many of them referring to the four-step model previously created in the UK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,44,45 A total of eight of the included studies were UK-based and outlined the steps to implementation of an APRT role in the UK. 21,23,24,32,35,36,42,43 These papers discussed the four step APRT framework established by the UK called the 'four domains of practice'. These four domains are set out by national guidance and comprise the following domains: Eleven of the studies reported on the establishment of an APRT role in Canada, 8,14,17,19,22,26,[29][30][31]33,35 many of them referring to the four-step model previously created in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…The APRT scope of practice varied between countries and departments as it was based on service needs. The roles and responsibilities expected of the APRT were discussed in 29 of the included studies, 6,[8][9][10]16,19,[21][22][23][25][26][27][30][31][32][33][34][35][37][38][39][40][41][42][43]46 though some papers provided much greater detail than others. The two main approaches in defining the APRT scope of practice were either site specific or service based.…”
Section: Scope Of Practice Of the Aprtmentioning
confidence: 99%
See 1 more Smart Citation
“…The line between ACP and routine clinical practice blurs with time. 10,28,35 A more adaptable model would be incorporating aspects of ACP into current roles. The challenges of gaining continuous funding with the need for regular training and auditing, increases resistance and places a strain on departments.…”
Section: Roles and Responsibilitiesmentioning
confidence: 99%
“…2,10,24 In some MRIgRT settings, TRs are already performing roles that were previously the remit of other MDT members to streamline the workflows and facilitate easier implementation. 24,25,26,27,28 In other MRIgRT centres, the number of treatment sites are increasing due to the success and tolerability of the pathway. 26,27,29 Good, 'standard' radiotherapy skills are a necessity for MRIgRT and subsequent role development 10,24 and is the case with other role extensions, advanced technique developments, and for existing ACP TR roles.…”
Section: Introductionmentioning
confidence: 99%